PENGARUH PEMBATASAN SOSIAL BERSKALA BESAR (PSBB) SELAMA PANDEMI COVID-19 TERHADAP TINGKAT PENJUALAN UMKM - Jonathan Lucky (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2021)
The Covid-19 pandemic has had an impact on various business sectors, including the MSME sector. The existence of restrictions on activities affects business activities in which business actors must limit the number of visitors. This will have an impact on the level of sales generated. The results of research conducted at one of the UMKM indicated that the existence of restrictions on social activities caused the level of sales to fluctuate. The lowest level of sales occurred at the beginning of the period of limiting social activities, then increased in line with the relaxation of restrictions on social activities.